Foot function during gait and parental perceived outcome in older children with symptomatic club foot deformity. (1st July 2020) - McCahill, Jennifer Leigh; Stebbins, Julie; Harlaar, Jaap; Prescott, Robin; Theologis, Tim; Lavy, Christopher
Abstract : Aims: To assess if older symptomatic children with club foot deformity differ in perceived disability and foot function during gait, depending on initial treatment with Ponseti or surgery, compared to a control group. Second aim was to investigate correlations between foot function during gait and perceived disability in this population. Methods: In all, 73 children with idiopathic club foot were included: 31 children treated with the Ponseti method (mean age 8.3 years; 24 male; 20 bilaterally affected, 13 left and 18 right sides analyzed), and 42 treated with primary surgical correction (mean age 11.6 years; 28 male; 23 bilaterally affected, 18 left and 24 right sides analyzed). Foot function data was collected during walking gait and included Oxford Foot Model kinematics (Foot Profile Score and the range of movement and average position of each part of the foot) and plantar pressure (peak pressure in five areas of the foot). Oxford Ankle Foot Questionnaire, Disease Specific Index for club foot, Paediatric Quality of Life Inventory 4.0 were also collected. The gait data were compared between the two club foot groups and compared to control data. The gait data were also correlated with the data extracted from the questionnaires. Results: Our findings suggest that symptomatic children with club foot deformity present with similar degrees of gait deviations and perceived disability regardless of whether they had previously been treated with the Ponseti Method or surgery. The presence of sagittal and coronal plane hindfoot deformity and coronal plane forefoot deformity were associated with higher levels of perceived disability, regardless of their initial treatment. Conclusion: This is the first paper to compare outcomes between Ponseti and surgery in a symptomatic older club foot population seeking further treatment. It is also the first paper to correlate foot function during gait and perceived disability to establish a link between deformity and subjective outcomes Cite this article: Bone Joint Open 2020;1-7:384–391.